Land-Reform Politics in South Africa's Countryside - Ntsebeza, Lungisile (Peace review (Palo Alto, Calif.), 2007)
The post-1994 South African government introduced a land reform in order to address racial land inequalities inherited from colonial rule and apartheid. White settlers appropriated more than 90 percent of the South African land surface. The extent of land dispossession in South Africa has no parallel in other African countries. The process began in the mid-seventeenth century, and was finalized in legal terms when the 1913 Act was promulgated. It destroyed black farming that, as Archie Mafeje and Cohn Bundy argue, adapted to commodity farming where Africans became the most dynamic agricultural producers in South Africa. In some parts of the country, the colonial government and missionaries went further and established a class of African fanners. Adapted from the source document.